Risk factors associated with hypoglycemia in newborns - Ynguil Amaya, Willam (2022)
A review paper was written aiming to determine risk factors related with hypoglycemia in newborns. Objectives were to determine clinical evidence for neonatal hypoglycemia-related risk factors and to determine the pathophysiological support upon risk factors implicated in the occurrence of hypoglycemia in newborns. Searches were performed in Medline-Pubmed, SCOPU, and HINARI, looking for papers published up to November 2021. We obtained 108 papers. It was concluded that although universal screening for hypoglycemia in asymptomatic low-risk newborns could be unnecessary, there is evidence that hypoglycemia may cause abnormalities in neurological development. Maternal risk factors for neonatal hypoglycemia include gestational diabetes, preeclampsia, and gestational obesity. Risk factors in newborns include sepsis, low birth weight and prematurity.